Wilson disease and other neurodegenerations with metal accumulations - Dusek, Petr; Litwin, Tomasz; Czlonkowska, Anna (Neurologic clinics, 2015)
Trace elements, such as iron, copper, manganese, and calcium, which are essential constituents necessary for cellular homeostasis, become toxic when present in excess quantities. In this article, we describe disorders arising from endogenous dysregulation of metal homeostasis leading to their tissue accumulation. Although subgroups of these diseases lead to regional brain metal accumulation, mostly in globus pallidus, which is susceptible to accumulate divalent metal ions, other subgroups cause systemic metal accumulation affecting the whole brain, liver, and other parenchymal organs. The latter group comprises Wilson disease, manganese transporter deficiency, and aceruloplasminemia and responds favorably to chelation treatment.
Keywords: Metals; Chelating therapy; Brain; Mental Disorders; NBIA; duševní poruchy; Manganism; Chelation Therapy; Neurodegeneration with brain iron accumulation; mozek; kovy; hepatolentikulární degenerace; Humans; Primary familial brain calcification; Wilson disease; Hepatolenticular Degeneration; chelátová terapie; lidé